Reprint of: COVID-19, lockdowns, and the municipal bond market - Tran, Nhu; Uzmanoglu, Cihan (Journal of Banking & Finance, 2023)
We study how investors in the US municipal bond market price the state lockdowns announced during the coronavirus (COVID) pandemic. To begin with, we examine the extent to which state-level COVID developments influence yield spreads of municipal bonds. We find that macro-level factors are the primary determinants of municipal bond spreads during the pandemic, but state-level COVID developments also matter at the margin. For instance, a doubling of new COVID cases in a state is associated with a 2% (1.4 basis points) increase in yield spreads of municipal bonds issued in that state. Accordingly, lockdowns may decrease municipal bond spreads by reducing COVID cases, but lockdowns may also increase them by reducing local economic activities. Overall, we find that yield spreads in both primary and secondary municipal bond markets increase by about 15% following lockdown announcements, suggesting that lockdown announcements increase the risk premiums investors require for holding municipal bonds.